Noblesse oblige?: determinants of survival in a life and death situation - Bruno S. Frey; David A. Savage; Benno Torgler (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper explored the determinants of survival in a life and death situation created by an external and unpredictable shock. We are interested to see whether pro-social behaviour matters in such extreme situations. We therefore focus on the sinking of the RMS Titanic as a quasi-natural experiment do provide behavioural evidence which is rare in such a controlled and life threatening event. The empirical results support that social norm such as women and children first survive in such an environment. We also observe that women of reproductive age have a higher probability of surviving among women. On the other hand, we observe that crew members used their information advantage and their better access to resources (e.g. lifeboats) to generate a higher probability of surviving. The paper also finds that passenger class, fitness, group size, and cultural background matter.
Keywords: D63; D64; D71; D81; 330; Decision under pressure; altruism; social norms; interdependent preferences; excess of demand; Soziale Beziehungen; Entscheidung; Altruismus; Soziale Norm; Konsuminterdependenz; Rationierung; Theorie; Feldforschung; Schiffsunfall; Großbritannien